2014
DOI: 10.1242/jcs.153049
|View full text |Cite
|
Sign up to set email alerts
|

P-Rex1 directly activates RhoG to regulate GPCR-driven Rac signalling and actin polarity in neutrophils

Abstract: G-protein-coupled receptors (GPCRs) regulate the organisation of the actin cytoskeleton by activating the Rac subfamily of small GTPases. The guanine-nucleotide-exchange factor (GEF) P-Rex1 is engaged downstream of GPCRs and phosphoinositide 3-kinase (PI3K) in many cell types, and promotes tumorigenic signalling and metastasis in breast cancer and melanoma, respectively. Although P-Rex1-dependent functions have been attributed to its GEF activity towards Rac1, we show that P-Rex1 also acts as a GEF for the Rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…A recent study showed that Rac binds to a PKA regulatory subunit and that PKA phosphorylates and activates PAK, setting up a model where PKA binds Rac-GTP to help in the stimulation of PAK and its downstream signals (45). It is also important to note that PREX1 is both activated by isoproterenol in cells and negatively regulated by PKA in vitro (10,31,32,46). One possible model that incorporates all of these data is that, after GPCR stimulation, G␤␥ signals to PREX1 to activate Rac and G␣ signals to PKA to help in the activation of PAK by Rac-GTP, and then these two events lead to PAK-mediated negative feedback on PREX1 to turn off Rac (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Rac binds to a PKA regulatory subunit and that PKA phosphorylates and activates PAK, setting up a model where PKA binds Rac-GTP to help in the stimulation of PAK and its downstream signals (45). It is also important to note that PREX1 is both activated by isoproterenol in cells and negatively regulated by PKA in vitro (10,31,32,46). One possible model that incorporates all of these data is that, after GPCR stimulation, G␤␥ signals to PREX1 to activate Rac and G␣ signals to PKA to help in the activation of PAK by Rac-GTP, and then these two events lead to PAK-mediated negative feedback on PREX1 to turn off Rac (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these DH domain-containing GEFs and DOCK family GEFs is currently unknown. Interestingly, however, a recent study indicated that P-Rex1 acts as a GEF for RhoG in vitro and its deficiency leads to a severe defect in fMLF-induced RhoG activation in neutrophils (37). Activated RhoG binds to ELMO, which then regulates localization and activation of DOCK-A subfamily members by interacting with their N-terminal regions (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…In neutrophils, P-Rex1 is a signal integrator activated by βγ subunits of heterotrimeric G proteins together with PtdIns-3,4,5-P 3 produced by p110γ. P-Rex1 stimulates a GTPase cascade involving RhoG and Rac, leading to activation of the NADPH oxidase as well as neutrophil migration (Damoulakis et al, 2014; Welch et al, 2002) (Figure 1). In cancer cells and growth factor-stimulated fibroblasts, PI3K activation drives Rac-mediated actin re-organization.…”
Section: The Pi3k Signaling Networkmentioning
confidence: 99%